Reproductive aspects of Notothenia rossii and N. coriiceps (Perciformes, Nototheniidae) at Potter Cove, 25 de Mayo (King George) Island during austral summer - Ferreira, Maria Florencia; Varela, María Luisa; Lo Nostro, Fabiana Laura; Ansaldo, Martin; Genovese, Griselda (Polar Biology)
Several fish species of the suborder Notothenioidei (Perciformes) predominate in the Antarctic Convergence Zone; nevertheless, reproductive studies are scarce due to difficulties on regular sampling. This study takes the research area of reproductive biology of notothenioids to a new level by providing, for the first time, data on sex hormone and vitellogenin detection in the blood of females of Notothenia rossii and N. coriiceps and correlates this data with morphological maturity indices as well as ovarian histology. Fish were captured during the Antarctic summer at Potter Cove, 25 de Mayo (King George) Island, and blood and ovary were collected. Histological analysis revealed that females of both fish possess group synchronous ovarian development with two distinct clutches of oocytes: a more advanced batch of vitellogenic oocytes ready for spawning and a second batch of previtellogenic oocytes for the next spawning event. Since liver vitellogenin synthesis is stimulated by estradiol produced by the ovaries, gonadal development, estradiol levels, and vitellogenin showed that both species were at a more advanced stage of maturation in March than in January. On the other hand and irrespectively of the month, gonadosomatic index and plasma estradiol levels of N. coriiceps were higher than those of N. rossii. Furthermore, females of N. coriiceps showed an advanced stage of vitellogenesis or were ready for spawn, contrary to results of previous studies. Our results indicate the successful use of gonadal morphology, estradiol, and vitellogenin detection for the estimation of sexual maturity stage of female adults. Fil: Ferreira, Maria Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología Experimental y Aplicada. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Biodiversidad y Biología Experimental y Aplicada; Argentina. Universidad de Buenos Aires. Facultad de ...